2016
DOI: 10.1093/jamia/ocv178
|View full text |Cite
|
Sign up to set email alerts
|

Computers in the clinical encounter: a scoping review and thematic analysis

Abstract: In contrast to the common negative views of HIT, it affects the clinical encounter in multiple ways. By applying identified strategies and best practices, HIT can support patient-clinician interactions rather than interfering with them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
124
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 65 publications
3
124
0
1
Order By: Relevance
“…However, concerns have arisen about the impact of EMRs on patient-physician relationships [3][4][5] and on the clerical burden for providers. 6 -8 Concerns regarding the impact of EMR use on patientphysician relationships have centered on the computer's negative influence on patient centeredness during the clinical encounter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, concerns have arisen about the impact of EMRs on patient-physician relationships [3][4][5] and on the clerical burden for providers. 6 -8 Concerns regarding the impact of EMR use on patientphysician relationships have centered on the computer's negative influence on patient centeredness during the clinical encounter.…”
mentioning
confidence: 99%
“…6 -8 Concerns regarding the impact of EMR use on patientphysician relationships have centered on the computer's negative influence on patient centeredness during the clinical encounter. [3][4][5] In addition, an unintended consequence of EMRs has been an increase in the clerical burden for practitioners, particularly for primary care providers (PCPs).…”
mentioning
confidence: 99%
“…First, we identified “sentence” as the unit of analysis/meaning, which identifies the level of the detail in the analysis. 21 Second, each transcript was reviewed several times to make sense of the data. Third, the entire team reviewed the initial 4 interviews for emergent codes and developed memos and preliminary interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…19,20 With the increased use and capabilities of EHRs and attention on patient centered care, the role of EHRs on patient centered care and patient engagement have become more notable. 21 Recent studies have increasingly focused on how EHR should be used and designed in more patient-centered ways. 22 Some of the studies have reported that EHR should be used as a communication and patient education tool (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The EHR improves the quality of biomedical data gathering and reduces the number of medical errors [813]. It also facilitates the sharing of medical information with the patient [1416].…”
Section: Introductionmentioning
confidence: 99%